DARI DE JAVASCHE BANK MENJADI BANK INDONESIA: STUDY KASUS BANK INDONESIA CABANG PADANG 1953-1970 - Erma, Erma (Fakultas Ilmu Sosial Universitas Negeri Padang, 2014)
Since the second half of the nineteenth century, the Dutch East Indies was marked by a new phase in banking development. The first bank was De Javasche Bank in Batavia, established on January 24, 1828 under the rules no. 28 in 1827. More than three decades (36 years) after the founding of De Javasche Bank in Batavia, the bank Â expanding its territory into the outer island of Java, namely to Padang. In this context it is interesting to discuss about the development of De Javasche Bank before and after bank transformed to Bank Indonesia Branch Padang until 1970. This type of research is the study of history. The research method used is heuristic, verification, source criticism, interpretation, and historiography. The results showed that since the establishment of De Javasche Bank on January 28, 1828 in Batavia, the bank has grown and transformed into the Central Bank in the New Order. The bank then serves as an agent of development and circulation bank and classifying banks in Indonesia. Key Words: De Javasche Bank, development, Netherlands Indies, independence era, Old Order era, New Order era